Selective Bromination of Graphene Oxide by the Hunsdiecker Reaction - Jankovský, Ondřej; Lojka, Michal; Luxa, Jan; Sedmidubský, David; Tomanec, Ondřej; Zbořil, Radek; Pumera, Martin; Sofer, Zdeněk (Chemistry (Weinheim an der Bergstrasse, Germany), 2017)
Halogenated graphenes have been attracting great attention in the recent years. The currently used methods are usually non-specific, and halogen groups are randomly distributed over the graphene. Here we demonstrate a selective graphene functionalization based on a well known reaction mechanism-Hunsdiecker reaction-applied on selective bromination of graphene oxide. The chemical analysis using various spectroscopic methods proved a high efficiency of this functionalization method. Bromination can be carried out under mild conditions without any high temperature or high pressure treatment. The chemical modification led to introduction of up to 20 wt.% of bromine covalently bonded to the graphene skeleton. The modified graphene was characterized in detail using a broad range of microscopic and spectroscopic methods and no significant contamination by reaction by-products was detected.
Keywords: halogen-graphene; graphene; graphene oxide; bromine